Sistem Penghitung Jumlah Orang Melewati Pintu Menggunakan Metode Background Subtraction Berbasis Raspberry Pi - Diego Yanda Setiawan; Hurriyatul Fitriyah; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The center state of the crowd such as shopping centers, libraries and so on are the places that many people visit. This data is very important because it can be used as interest indicator. In this research is needed a system which can provide an information about the number of visitor so manager can do monitoring of the place. Possible technologies in making this system is to uses digital image processing and computer vision. Background Subtraction Method useful to detect moving objects. From the test results, the Background Subtraction method can detect moving objects very well, opening and closing can improve image results. The success rate when one person enter is 87,5% and exit is 87,5%, The Accuracy when two persons enter at the same time is 87,5% and exit is 100%. Overall the Average accuracy obtained by this system with a certain angle camera when one person enter is 75% and exit is 78.75%, The Accuracy when two persons enter and exit at the same time is 71% and 71%. Also the best camera angle while capture images when one person pass is 70°,80°, 90°. when two person pass at the same time 50°, 70°.